Use the properties of operations to add 4(g−2)+(g+2)

.(1 point)

1 answer

To simplify the expression \( 4(g - 2) + (g + 2) \), we can follow these steps using the properties of operations:

  1. Distribute \( 4 \) into the first term: \[ 4(g - 2) = 4g - 8 \]

  2. Rewrite the expression: \[ 4(g - 2) + (g + 2) = (4g - 8) + (g + 2) \]

  3. Combine like terms:

    • Combine \( 4g \) and \( g \): \[ 4g + g = 5g \]
    • Combine constants \( -8 \) and \( 2 \): \[ -8 + 2 = -6 \]
  4. Put it all together: \[ 5g - 6 \]

Thus, the simplified expression is \( 5g - 6 \).